1999
DOI: 10.1152/physrev.1999.79.1.s77
|View full text |Cite
|
Sign up to set email alerts
|

Control of CFTR Channel Gating by Phosphorylation and Nucleotide Hydrolysis

Abstract: Control of CTFR Channel Gating by Phosphorylation and Nucleotide Hydrolysis. Physiol. Rev. 79, Suppl.: S77-S107, 1999. - The cystic fibrosis transmembrane conductance regulator (CFTR) Cl- channel is the protein product of the gene defective in cystic fibrosis, the most common lethal genetic disease among Caucasians. Unlike any other known ion channel, CFTR belongs to the ATP-binding cassette superfamily of transporters and, like all other family members, CFTR includes two cytoplasmic nucleotide-binding domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
434
2
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(452 citation statements)
references
References 185 publications
8
434
2
6
Order By: Relevance
“…1, lanes 3 and 5, for HT29 and SMC, respectively. These results demonstrated that CFTR endogenously expressed in SMC can be phosphorylated in vitro by PKA as in epithelial cells (10,11,18).…”
Section: Identification Of Cftr In Smc By Immunoprecipitation and In mentioning
confidence: 81%
See 2 more Smart Citations
“…1, lanes 3 and 5, for HT29 and SMC, respectively. These results demonstrated that CFTR endogenously expressed in SMC can be phosphorylated in vitro by PKA as in epithelial cells (10,11,18).…”
Section: Identification Of Cftr In Smc By Immunoprecipitation and In mentioning
confidence: 81%
“…Since CFTR has been detected in ventricular heart cells (11)(12)(13)(14), we raised the question of its expression in vascular cells. We first searched for the presence of CFTR in SMC at a protein level.…”
Section: Identification Of Cftr In Smc By Immunoprecipitation and In mentioning
confidence: 99%
See 1 more Smart Citation
“…As channel gating is controlled by both PKA phosphorylation of the R region and ATP binding and hydrolysis at the NBDs, we hypothesized that the R region has direct phosphorylation-dependent interactions with the NBDs 21 . To test this hypothesis, we have performed NMR studies of the structural properties of the isolated R region in both the nonphosphorylated and PKA-phosphorylated states, and of the interaction between the R region and NBD1.…”
mentioning
confidence: 99%
“…Cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel belonging to the ABC transporter family (43). CFTR regulates salt and water transportation across epithelial membranes in lung and gut.…”
Section: S-glutathionylation Of Cystic Fibrosis Transmembrane Conductmentioning
confidence: 99%